Crystalline phase dependent electrical properties of Mg incorporated tetragonal phase stabilized ZrO2 high-κ dielectric layer in Si based MOS capacitors. (July 2018) - Bhanu, J. Udaya; Amutha, A.; Babu, G. Ramesh; Sundaravel, B.; Thangadurai, P.
Abstract: Electron beam evaporated Mg doped ZrO2 (Mg:ZrO2 ) high-k thin films on p-type Si(100) substrate and their metal oxide semiconductor (MOS) capacitors were structurally and electrically studied. Thicknesses of the dielectric films were in the range from 85 to 240 nm with RMS roughness between 1.4 and 2.3 nm. The targets for e-beam evaporation were made with well characterized pure ZrO2 with monoclinic phase and with 3%Mg doped tetragonal phase stabilized ZrO2 nanopowders. Structural phase analysis revealed that the phases of Mg:ZrO2 thin films deposited have retained their respective phases of zirconia targets used. The incorporation of Mg ions in ZrO2 dielectric gate layer had increased the width of the hysteresis window in the C-V characteristics. Various leakage current conduction mechanisms in the accumulation region of the MOS capacitors have been used to understand the leakage current mechanism and found that traps present in the oxide layer played a major role in explaining the leakage current. In particular, the conduction mechanisms such as Poole-Frenkel emission, Space Charge Limited Conduction and Trap-assisted tunneling were found to be dominant in these devices. A high dielectric constant of 28.9 was achieved in the Mg doped tetragonal phase stabilized ZrO2 gate oxide films with a leakage current density of 3.32 × 10 −6 A/cm 2 at − 1 V. Hence, the tetragonal phase stabilized Mg:ZrO2 gate oxide layer showed improved electrical characteristics making them potential for memory storage devices.